2021
DOI: 10.30802/aalas-jaalas-20-000123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mitochondrial Function and Developmental Potential of Mouse Oocytes after Mitoquinone Supplementation during Vitrification

Abstract: Vitrification negatively affects the mitochondrial membrane potential (ΔΨm) in oocytes while also leading to increased reactive oxygen species (ROS), ATP depletion and induction of apoptosis in oocytes. Mitoquinone (MitoQ) is an antioxidant that protects mitochondrial membrane integrity from ROS. This study examined the effect of adding MitoQ to vitrification medium on mitochondrial function and embryo development in vitrified oocytes. Metaphase II (MII) stage oocytes were collected from NMRI mouse ovaries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Previous research has established that vitrification causes a significant increase in the level of ROS in oocytes [70,71], leading to lipid peroxidation and damaging DNA, proteins, and enzyme activity [72]. Similarly, vitrification obviously facilitated the ROS generation of bovine oocytes in our results (Figure 3B).…”
Section: Discussionsupporting
confidence: 78%
“…Previous research has established that vitrification causes a significant increase in the level of ROS in oocytes [70,71], leading to lipid peroxidation and damaging DNA, proteins, and enzyme activity [72]. Similarly, vitrification obviously facilitated the ROS generation of bovine oocytes in our results (Figure 3B).…”
Section: Discussionsupporting
confidence: 78%
“…MitoQ has been reported to promote maturation of porcine oocytes in vitro by maintaining mitochondrial homeostasis and suppressing UCP2 levels to maintain the stability of mitochondrial heat production [ 16 , 17 ]. In addition, MitoQ has been reported to reduce ROS produced by vitrification and freezing of oocytes, thereby increasing cell viability and fertility [ 18 ]. In addition to protecting the mitochondria, MitoQ may improve spindle and chromosome defects in oocytes exposed to oxidative stress and in oocytes from aged mice during in vitro maturation (IVM) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicated that large amounts of ROS generated during vitrification would result in oxidative stress which reduced oocytes developmental potential ( Shirzeyli et al, 2021 ). Therefore, it was not surprisingly that genes involved in oxidative stress-related pathway, the PI3K/AKT/mTOR pathway, was differentially expressed in our study.…”
Section: Discussionmentioning
confidence: 99%